Wage justice in the management of Islamic educational institutions: An analysis of the Hadith “give the worker his wage before his sweat dries” - Trian Hermawan; Muhammad Akmansyah (Priviet Social Sciences Journal, 2026)
This study examines wage justice in Islamic educational institutions through an analysis of the Prophetic hadith “Give the worker his wages before his sweat dries” (HR. Ibn Majah) and its relevance to contemporary human resource management. The study is motivated by persistent issues such as delayed wage payments, inadequate compensation, and structural inequalities affecting educators.Using a qualitative approach with a library research design, this study integrates normative analysis of hadith and fiqh literature with contemporary theories of organizational justice, including distributive, procedural, and temporal justice. The findings reveal that the hadith embodies a multidimensional framework of wage justice that aligns with modern management theory while extending it through ethical and spiritual accountability. However, a significant gap persists between these normative principles and institutional practices, driven by managerial limitations, structural inequality, and cultural narratives that undermine professionalism. In response, this study proposes an integrative model of fair wage management based on competence, welfare adequacy (kifayah), timely payment systems, and transparent contractual governance. The study concludes that wage justice in Islam constitutes an institutional obligation that must be operationalized within organizational systems. The proposed model offers both theoretical and practical contributions by bridging Islamic ethical principles with contemporary management practices. Future research is recommended to empirically validate the model across diverse educational contexts.